Successful healing of aneurysmal false lumen using a second-generation drug-eluting stent in spontaneous coronary artery dissection: a case report - Tomiharu Niida; Kikuo Isoda; Miho Tada; Satoshi Kitahara; Yusuke Fujino (The Egyptian Heart Journal, 2024)
Abstract Background According to 2023 ESC Guideline, conservative medical management is generally recommended for the treatment of spontaneous coronary artery dissection (SCAD) except for patients with signs of ongoing myocardial ischemia. However, in some cases, invasive treatment (coronary artery bypass graft surgery or percutaneous coronary intervention (PCI)) is performed because of the progression of aneurysm in SCAD. Although there is no established strategy for the management of coronary aneurysm in SCAD, we report a case of successful healing of aneurysmal false lumen (AFL) using a second-generation drug-eluting stent (DES) in SCAD. Case presentation A 44-year-old woman without any cardiovascular risk factors was transferred to our hospital due to inferior myocardial infarction. Coronary angiography (CAG) showed multiple SCADs in the coronary artery. We performed PCI to the distal right coronary artery (RCA) because the RCA showed severe stenosis (99%) with bradycardia. Six days after the first PCI, SCAD relapsed in the mid left anterior descending artery (LAD). Furthermore, AFL was observed by intravascular ultrasound imaging. To avoid enlargement of the AFL and progression of the dissection toward the proximal site of the LAD, we performed PCI to the mid LAD to seal the entry tear of the dissection using a second-generation DES. CAG revealed that the AFL in the mid LAD completely diminished at 1 year after PCI. Conclusions The implantation of a second-generation DES might be one of therapeutic options for sealing AFL in SCAD patients.